Pengaruh Pemberian Madu sebagai Terapi Komplementer pada Balita dengan Diare: Literature Riview - Eki Nurhakiki; Miftahul Falah S.kep.,Ns.,MSN.Ph.d (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2025)
Diarrhea in toddlers, characterized by more than three watery stools per day, often leads to dehydration, electrolyte imbalance, and increased morbidity, making effective management essential. Standard treatments such as oral rehydration salts (ORS) and zinc are beneficial, yet symptom improvement may occur slowly, prompting the need for safe and accessible complementary therapies. Honey, a natural substance rich in enzymes, simple carbohydrates, and antibacterial compounds, has the potential to accelerate recovery by supporting mucosal healing and enhancing rehydration. This literature review aimed to analyze evidence regarding the effectiveness of honey as a complementary therapy for diarrhea in toddlers by reviewing articles published from 2020 to 2025 through Google Scholar and the Garuda Portal using the keywords “intervention,” “honey therapy,” “diarrhea,” and “children.” The results of the literature riview produced five articles met the inclusion criteria, consisting of original studies with pre-experimental, quasi-experimental, or case study designs involving toddlers aged 1–5 years who received oral honey as an intervention. Thematic analysis showed that all included studies reported a decrease in stool frequency and improved stool consistency within 2–3 days of honey administration, along with increased appetite and improvement in mild clinical symptoms. These findings indicate that honey can serve as an effective complementary therapy to support diarrhea management in toddlers. However, further research using randomized controlled trials with larger sample sizes is needed to strengthen the existing clinical evidence.